2018
DOI: 10.1111/ggi.13450
|View full text |Cite
|
Sign up to set email alerts
|

Use of proton pump inhibitors is associated with increased mortality due to nosocomial pneumonia in bedridden patients receiving tube feeding

Abstract: The use of PPI in bedridden tube-fed patients was independently associated with mortality due to nosocomial pneumonia, and the PPI group had a non-significant lower incidence of gastrointestinal bleeding than the non-PPI group. Geriatr Gerontol Int 2018; 18: 1215-1218.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
8
0
2
Order By: Relevance
“…As HAP is often associated with peptic disease and nonsteroidal drugs are usually used to allay patients' fever, the administration of proton-pump inhibitor was common in HAP patients. In the current study, we found that the administration of proton-pump inhibitor had a negative effect on HAP patients' 30-day mortality, consistent with the literature report [16]. Whether patients received antibiotic therapy in the preceding 90 days showed a significant difference in the outcomes of the present study, suggesting its importance as a prognostic factor for 30-day mortality with HAP.…”
Section: Discussionsupporting
confidence: 91%
“…As HAP is often associated with peptic disease and nonsteroidal drugs are usually used to allay patients' fever, the administration of proton-pump inhibitor was common in HAP patients. In the current study, we found that the administration of proton-pump inhibitor had a negative effect on HAP patients' 30-day mortality, consistent with the literature report [16]. Whether patients received antibiotic therapy in the preceding 90 days showed a significant difference in the outcomes of the present study, suggesting its importance as a prognostic factor for 30-day mortality with HAP.…”
Section: Discussionsupporting
confidence: 91%
“…Association between PPI use and all-cause mortality is difficult to interpret due to the large variance in patients studied to date. PPI use has been associated with increased mortality in cancer patients, liver cirrhotics, and those requiring artificial nutrition [22][23][24]. However, these patient cohorts are dissimilar to the CKD population, and thus of limited use in determining true risk.…”
Section: Discussionmentioning
confidence: 99%
“…Two, small cohort studies on patients with liver cirrhosis and bedridden patients requiring tube feeds also showed a positive association with PPI use and increased overall mortality. 21,22 However, another larger cohort study showed decreased 90 day mortality in hip fracture patients who were started on PPIs during their hospital stay. 23 Yet another study done by Xie and colleagues showed a small excess of cause speci c mortality due to cardiovascular disease, chronic kidney, disease, and upper gastrointestinal cancer in patients taking PPIs.…”
Section: Discussionmentioning
confidence: 99%